Structured reporting of solid and cystic pancreatic lesions in CT and MRI: consensus-based structured report templates of the German Society of Radiology (DRG) = Strukturierte Befundung von soliden und zystischen Pankreasläsionen im CT und MRT : konsensus-basierte Befundvorlagen der Deutschen Röntgengesellschaft (DRG) - Persigehl, Thorsten; Baumhauer, Matthias; Baeßler, Bettina; Beyer, Lukas Philipp; Bludau, Marc; Bruns, Christiane; Bunck, Alexander Christian; Germer, Christoph-Thomas; Grenacher, Lars; Hackländer, Thomas; Haneder, Stefan; Heinrich, Stefan; et al. (RöFo, 2020)
Background: Radiological reports of pancreatic lesions are currently widely formulated as free texts. However, for optimal characterization, staging and operation planning, a wide range of information is required but is sometimes not captured comprehensively. Structured reporting offers the potential for improvement in terms of completeness, reproducibility and clarity of interdisciplinary communication. Method: Interdisciplinary consensus finding of structured report templates for solid and cystic pancreatic tumors in computed tomography (CT) and magnetic resonance imaging (MRI) with representatives of the German Society of Radiology (DRG), German Society for General and Visceral Surgery (DGAV), working group Oncological Imaging (ABO) of the German Cancer Society (DKG) and other radiologists, oncologists and surgeons. Results: Among experts in the field of pancreatic imaging, oncology and pancreatic surgery, as well as in a public online survey, structured report templates were developed by consensus. These templates are available on the DRG homepage under www.befundung.drg.de and will be regularly revised to the current state of scientific knowledge by the participating specialist societies and responsible working groups. Conclusion: This article presents structured report templates for solid and cystic pancreatic tumors to improve clinical staging (cTNM, ycTNM) in everyday radiology. Key Points: Citation Format
Gesehen am 21.01.2020